Penerapan Strategi Stad Untuk Meningkatkan Keaktifan Dan Hasil Belajar Ipa Siswa Kelas V Di Mim Sidodadi Masaran Sragen Tahun 2015/2016 - RAHAYU, LESTARI DWI (2016)
ABSTRACT Lestari Dwi Rahayu / A510120064. Application of STAD Strategy to Improve Learning Outcomes Science Activity and Grade V in MIM Sidodadi Masaran Sragen. Essay, Department of Primary School Teacher Education, the Faculty of Education, University of Muhammadiyah Surakarta. February 2016. This research applying learning strategies Student Teams Achievement Division (STAD) which aims to: 1) enhance the activity of MIM Sidodadi fifth grade students Masaran Sragen year 2015/2016, 2) improve learning outcomes Natural Sciences in Class V MIM Sidodadi Masaran Sragen 2015 / 2016. This type of research action research. Fifth grade students study subjects MIM Sidodadi Masaran Sragen totaling 19 children. The technique of collecting data through observation and tests. The data analysis technique used is interactive analysis starts from data reduction, data presentation and then draw conclusions. The validity of the data using triangulation of data sources for observation activity and content validity of the test results of learning. The results showed an increase in the activity: 1) the activity of pre-cycle by a teacher at the liveliness of students classified 78.94% and 21.05% less quite enough, by a student researcher 89.47% 10.52% less active and fairly, 2) the first cycle of the first meeting by teacher observation that active students increased by 36.84% 21.05% active student researcher, 3) the first cycle of students active petemua II 68.42%, 47.36% by investigators, 4) the second cycle of meeting I by the results of a very active student teacher obserasi 42.10%, by researchers, 36.84%, 5) second cycle students are very active meeting II 89.47%, 84.21% by investigators. The results of the research study results showed: 1) pre-cycle, less knowledgeable 63.15%, 26.31% perpengetahuan enough, good knowledge 10.52% and only 10.52% of all students who go beyond KKM, 2) iklus I 5 , 26% less knowledgeable, 26.31% perpengetahuan enough, good knowledge 47.36%, 21.05% excellent knowledgeable, 3) the second cycle shows, 52.63% good knowledge, excellent knowledgeable 47.36%, and 89.47% of all students reach KKM. The conclusion of this study were: 1) STAD can enhance the activity of students in the fifth grade science teaching MIM Sidodadi Masaran Sragen, 2) STAD strategy to improve learning outcomes IPA in MIM Sidodadi Masaran Sragen.